LEXICOGRAPHICAL ASPECT OF THE SLOVENIAN MULTI-WORD LEXEMES (Philological Studies, 2019)
This paper builds on the analysis of the semantic properties of slovene multi-word lexemes with potential terminological meaning which are most relevant from a lexicographical perspective. Semantic properties are analyzed from the perspective of transformational (generative) word-formation theory, the distinctive semantic features (semes) and semantic derivation respectively semantic transfers which contribute to new syntactic-semantic combinations of individual compounds of a phrase, to the consequent merger of their meanings to form a single meaning of a set phrase and to a higher level of lexicalization and firmness of a multi-word lexeme.
Keywords: lexicography, lexicalization, multi-word lexeme, semantic derivation, semantic feature, semantic merger, semantic transfer, transformational (generative) word-formation theory